Effects of uncut refuge management on grassland arthropods – A systematic review - Kitti Révész; Róbert Gallé; Jean-Yves Humbert; Péter Batáry (Global Ecology and Conservation)
European semi-natural grasslands are often managed by mowing. These habitats have species-rich fauna, but mowing threatens arthropods’ abundance and diversity. Leaving some part of the vegetation uncut can play a crucial role in their survival during and after mowing. The effectiveness of such uncut refuges for the conservation of arthropods has been studied, but the results are contradicting and partial. We conducted a systematic review of 22 articles encompassing 66 observations to synthesise existing knowledge. Overall, 69 % of abundance observation data and 64 % of species richness observation data showed positive responses to uncut refuges. In comparison, the remaining observations showed negative (25 % for abundance, 26 % for species richness) and neutral (6 % for abundance, 10 % for species richness) effects. We found several potential drivers behind these patterns, including refuge shape – most commonly strips or blocks – and refuge proportion, typically 10–25 % of the area. Results varied across study designs, which often involved sampling arthropods within and outside the refuges, before or after mowing, with or without independent control meadows. Additionally, research primarily focused on orthopterans with no negative responses to refuges, whereas other taxa received less attention. Although further research is needed on the assumed moderators (e.g. grassland habitat type, landscape structure) and understudied grassland taxa, based on the existing knowledge, we recommend leaving refuges where arthropod conservation is concerned.